AGRO COMMERCIAL COOPERATIVE EFFORTS (KAN) JABUNG SHARIA IN IMPROVING THE WELFARE OF DAIRY COW FARM MEMBERS - Muslim, Saiful; Firmansyah, Ahmad Rizal (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The purpose of this study is to find out the efforts and roles by the KAN Jabung Agro-Commerce Cooperative, Kab. Malang, East Java in enhancing its members' welfare, especially those who work as dairy farmers. This research is field research using direct interviews with managers and dairy farmers about how to conduct training so that their financial earning grows, a descriptive qualitative is utilised to interpret data. The results of research on economic and political concepts are summarized from various social values, including training programs for raising dairy cows, financial management training, routine counseling, providing financing with low margins, financing for buying cows, repairing stables. With this program, the KAN Jabung Syariah Agro-Commerce Cooperative is committed with members to enhance the welfare of members even though there are many factors that support and inhibit the program.